Introducing Imam Ibn Bilal Al-Hanafi, 957 AD and his scientific impact - Althobaiti, Reem Ahmed (Journal of Islamic Sciences, 2022)
This study aims to identify one of the tenth-century notables and to investigate his scientific impact. This scholar is known as Muhammad bin Muhammad, Abu Abdullah, Shams Al-Din, also called Ibn Bilal, Al-Ayni of origin. He was born and died in Al-Halabi. His doctrine was Al Hanafi.The study was conducted by investigating and comparing the translated sources of Ibn Bilal according to their chronological sequence. Also, it includes the manuscripts and libraries indexes, proof and scientific licenses along with uses of the manuscript of Ibn Bilal’s workbooks according to the descriptive and analytical approach.In summary, I found that the sources of Imam Ibn Bilal's translation have shortened his translation briefly, and it can be completed by verifying his books that are still in manuscript.
Keywords: Ibn Bilal; Abu Abdullah Ibn Bilal; Muhammad bin Muhammad Shams al-Din